Skill Level, Bottom Passing and Upper Passing in Volleyball, Extracurricular Participants of Junior High School 3 Banjarbaru - Navia Paramita; Mita Erliana; Norma Anggara (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
The aim of this research is to determine the level of lower passing and upper passing skills of extracurricular participants at Junior High School 3 Banjarbaru. This research method is descriptive quantitative with tests measuring the lower passing and upper passing skills of volleyball in extracurricular participants at Junior High School 3 Banjarbaru. The results of research on men’s underpassing were classified as very good 20%, good classification 20%, moderate 20%, poor 30%, very poor 10%, research results on female underpassing were classified as very poor 100%. The results of the passing research on boys were classified as very good 20%, good 20%, moderate 20%, poor 30%, very poor 10%, the results of the research on passing on girls were classified as very less than 100%. The conclusion of the research results is that the lower passing of the sons of extracurricular participants at Junior High School 3 Banjarbaru is poor, and the girls’ passing is very poor. The conclusion of the research results is that the passing of the sons of extracurricular participants at Junior High School 3 Banjarbaru is poor, and the daughters are very poor.